Crash analysis and evaluation of vehicular impacts on W-beam guardrails placed on sloped medians using finite element simulations. (October 2017) - Gutowski, Matthew; Palta, Emre; Fang, Howie
Highlights: Developed FE models of W-beam guardrails with different designs. Performed nonlinear FE simulations of vehicles crashing into guardrails on sloped medians. Evaluated the performance of single- and double-faced guardrails at MASH TL-3 conditions. Evaluated the performance of single-faced guardrails with and without a horizontal curvature. Abstract: With an average of six billion miles traveled per day on U.S. highways, according to the Federal Highway Administration (FHWA), transportation safety is of the utmost importance. Over the years, various traffic barrier systems, including W-beam guardrails, have been developed to reduce the number and severity of vehicle crashes. Despite their general effectiveness, improvements could be made, especially when installed on unlevelled terrains such as sloped medians. The destructive nature of crashes imposes significant challenges to barrier design using full-scale physical testing; numerical simulations thus become a viable means to support crash analysis, performance evaluation, and barrier designs. In this study, validated vehicle and W-beam models were used to perform full-scale simulations of vehicle-guardrail impacts. Fourteen single-faced and double-faced NCDOT W-beam guardrails (with placement heights of 29 and 31 inches) placed along a six-lane 46-foot median divided highway with 2.5H:1 V and 4H:1 V slopes were evaluated under front-side and backside vehicular impacts. The guardrails performance was determined by evaluating the vehicular responses based on MASH exit-box criterion, post-impact exit trajectory, yaw, pitch, and roll angles, transverse displacements, and transverse velocities.